Rapid formation of hydrogen-producing granules in an anaerobic continuous stirred tank reactor induced by acid incubation - Zhang, Zhen-Peng; Show, Kuan-Yeow; Tay, Joo-Hwa; Liang, David Tee; Lee, Duu-Jong; Jiang, Wen-Ju (Biotechnology and bioengineering, 2007)
A novel approach to rapidly initiate granulation of hydrogen‐producing sludge was developed in an anaerobic continuous stirred tank reactor at 37°C. To induce microbial granulation, the acclimated culture was subject to an acid incubation for 24 h by shifting the culture pH from 5.5 to 2.0. The culture was resumed to pH 5.5 after the incubation and the reactor was operated at hydraulic retention times (HRTs) of 12, 6, 2, 1, and 0.5 h in sequence. Microbial aggregation took place immediately with the initiation of acid incubation and granules were developed at 114 h. No granule was observed in the absence of acid incubation in the control test. Changing the culture pH resulted in improvement in surface physicochemical properties of the culture favoring microbial granulation. The zeta potential increased from −11.6 to −3.5 mV, hydrophobicity in terms of contact angle improved from 31° to 43° and extracellular proteins/polysaccharides ratio increased from 0.2 to 0.5–0.8. Formation of granular sludge facilitated biomass retention of up to 32.2 g‐VSS/L and enhanced hydrogen production. The hydrogen production rate and hydrogen yield increased with the reduction in HRT at an influent glucose concentration of 10 g/L once steady granular sludge layer was formed, achieving the respective peaks of 3.20 L/L · h and 1.81 mol‐H2/mol‐glucose at 0.5 h HRT. The experimental results suggested that acid incubation was able to initiate the rapid formation of hydrogen‐producing granules by regulating the surface characteristics of microbial aggregates in a well‐mixed reactor, which enhanced the hydrogen production. Biotechnol. Bioeng. 2007;96:1040–1050. © 2006 Wiley Periodicals, Inc.